One-stage posterior debridement and fusion combined with irrigation and drainage for the treatment of postoperative lumbar spondylodiscitis - Tao Zhang; Jianzhong Hu; Jianhuang Wu; Jinyang Liu; Shuangfei Ni; Chunyue Duan (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to evaluate the clinical outcomes of one-stage posterior debridement, interbody fusion, and instrumentation, combined with irrigation and drainage, for treating lumbar spondylodiscitis. Methods: The study included 23 patients (13 male and 10 female, mean age: 45 years) who had posterior debridement, interbody fusion, and instrumentation, followed by continuous closed irrigation and drainage for lumbar postoperative spondylodiscitis. The visual analog scale, Oswestry disability index, and lumbar lordosis angle were assessed before and after surgery to evaluate the clinical outcome. Results: The mean follow-up time was 27 (24–36) months. All patients tolerated the procedure well, and there were no instances of spondylodiscitis recurrence, though a dorsal dermal sinus developed in one patient after surgery. Infection was eliminated, as evidenced by the normalization of the erythrocyte sedimentation rates and C-reactive protein levels. The mean visual analog scale scores were significantly decreased after the operation. The mean lumbar lordosis angle before surgery was 21.61 ± 6.88° and the angle at the final follow-up was 31.61 ± 4.24°. The mean Oswestry disability index scores improved significantly both after the operation and at the follow-up visits (p < 0.05). Bone union was confirmed in all patients at a mean of 8.6 months post-operation, though this was not achieved until 2 years post-operation in one patient. All 3 patients who had neurological deficits showed great improvement at the last follow-up. Conclusion: Surgical management using one-stage posterior debridement, interbody fusion, and instrumentation, followed by continuous closed irrigation and drainage, might be an effective treatment option for lumbar postoperative spondylodiscitis. Level of evidence: Level IV, Therapeutic study. Keywords: Postoperative lumbar spondylodiscitis, Posterior surgery, Interbody fusion, Instrumentation, Closed irrigation and drainage